The ism-aggression. When a suffix Is equivalent to physical aggression - Velardi, Andrea (Rivista Italiana di Filosofia del Linguaggio, 2023)
The aim of this paper is to analyze the phenomenon of the what we could call Ism-Aggression in the Italian contest regard the use of some particular word such as fascist, comunist, sovereignist, nazionalist, populist, sexist, racist, specist, conspirationist accomplished through an instrumentally detaching of the terms from their own historical and political background and a surreptitious exploiting of the mechanism of the polarization and the ingroup/outgroup dynamics in order to generate a verbal aggression that is similar to a physical aggression. The Ism-Aggression generates epistemic and discursive injustice combining esercitive and verdictive authoritative speech acts, but it masks the explicit aggression of a manifest hate speech becoming a very effective rhetoric tool in the mediatic and Internet comunicative environment. The ism-aggression terms don’t overpass the counterpart test as one cannot substitute the word fascist with conservative and communist with socialist as one cannot otherwise substitute the italian slur terrone with southern. The ism-aggression term has not a counterpart because it works like an insult, like a slur.